Seismic performances of reinforced concrete buildings with openings in unreinforced masonry infill walls: a soil–foundation–structure modelling approach - Amritha, Nath; Prasanth, S. (Frontiers in Built Environment, 2025)
This study aims to capture the impacts of soil–structure interactions on infill openings in unreinforced-masonry-infilled mid-rise and high-rise reinforced concrete buildings. The soil–foundation–structure modelling method was adopted herein to incorporate the effects of the soil–structure interactions using the finite element software PLAXIS 3D. A six-storey and an eleven-storey reinforced concrete buildings with varying infill opening percentages of 20%, 30%, and 40% were considered in this work to resemble realistic door/window openings. Both building models were subjected to dynamic analyses under bidirectional loading by considering soft and stiff soil conditions. The maximum roof displacement, inter-storey drift ratio, mode shapes, and damage state levels were set as the performance assessment parameters. It was observed that the inter-storey drift ratio increased significantly for all models under soft soil conditions, especially in the case of 40% infill opening. The HAZUS methodology was used to assess the damage state level at each storey level. The mid- and high-rise buildings reached a maximum of moderate and moderate–extensive damage state levels, respectively, at 30% infill opening under both soil conditions; further, fixed-base conditions consistently underestimated the storey damage state levels. Based on the performance assessment parameters, optimum infill opening values of 40% and 30% were estimated for the mid-rise and high-rise buildings, respectively, under stiff soil conditions; however, these optimal percentages were significantly reduced to 30% and 20%, respectively, under soft soil conditions. The above findings indicate that the soil conditions and building heights have significant impacts on infill opening percentages and affect the seismic performances of buildings. Thus, we conclude that soil–foundation–structure modeling is important for accurate seismic assessments, particularly in areas prone to high seismic activities.